2021
DOI: 10.2147/opth.s304735
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens Use Patterns, Behavior and Knowledge Among University Students in Thailand

Abstract: Purpose: Little is known about contact lens (CL) use in young generation. This study aimed to investigate the patterns, behavior and knowledge of CL wear and care in Thai university students. Methods: A cross-sectional study using online questionnaires was conducted during July 2019 to February 2020 in two Rajabhat universities, Bangkok, Thailand. Participant characteristics, CL information, knowledge and behaviors were collected. Factors associated with poor behaviors and CL-related corneal ulcers were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 45 publications
9
28
3
Order By: Relevance
“…The cross-sectional study is not an appropriate approach for establishing the causative associations among the study variables, which is consistent with what other authors found [8,11]. Also, non-response bias is a problem in such studies, consistent with other research [12]. The problem stems from the self-reported questionnaire utilized in the present paper, which is consistent with other studies [12,10] and contrary to another body of studies [13,14].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The cross-sectional study is not an appropriate approach for establishing the causative associations among the study variables, which is consistent with what other authors found [8,11]. Also, non-response bias is a problem in such studies, consistent with other research [12]. The problem stems from the self-reported questionnaire utilized in the present paper, which is consistent with other studies [12,10] and contrary to another body of studies [13,14].…”
Section: Discussionsupporting
confidence: 88%
“…Also, non-response bias is a problem in such studies, consistent with other research [12]. The problem stems from the self-reported questionnaire utilized in the present paper, which is consistent with other studies [12,10] and contrary to another body of studies [13,14]. Therefore, future studies should utilize various methods, like interviews.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 6 Among university students in Thailand, poor CL behaviours were related to purchasing lenses from the internet, wearing them for over one year, and long wear duration (>12 hours). 7 A number of studies provide information on the prevalence of usage, knowledge, and risky behaviours of CL care, especially in young populations. 7–9 However, there are limited studies about the relationship between the behaviour and compliance of CL users in the general population in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous reports lack information on healthy patients aged < 40 years and none of the reports evaluated the healthy morphology. Because patients who use contact lens for refractive correction tend to be relatively young 18 , it is essential to determine the value and distribution of corneal endothelial density and morphology of healthy young patients for the accurate assessment of contact lens usage. Therefore, we aimed to analyze corneal ECD and morphology in healthy Japanese individuals without a history of contact lens usage, ophthalmic surgery, or ocular disease.…”
Section: Introductionmentioning
confidence: 99%